Predicting Tensile Properties of Lalang Grass Fiber (LGF) Reinforced Polypropylene (PP) using Mathematical Modelling - Mohamad Redzuan, Intan Fazreenna (IRC, 2020)
Fiber reinforced-polymer composite is commonly used in many fields due to its advantages such as low cost, renewability and biodegradable factors. Very limited efforts have been done on theoretical modelling of short fiber reinforced polymer. Moreover, the use of mathematical modelling for predicting the tensile properties of lalang grass fiber (LGF) reinforced with polypropylene (PP) is almost non-existence. Therefore, the objectives of this project were to predict the tensile properties of PP/LGF composite using mathematical modelling and to validate the theoretical values with the previous experimental results. The composition of the PP/LFG that was used to validate the prediction is 70/30 wt.%.